Alkaline Protease Production from Industrial Waste by Bacillus subtilis ML-4: Alkaline Protease Production from Industrial Waste (Biological Sciences - PJSIR, 2010)
The influence of various culture conditions on protease production by Bacillus subtilis ML-4 was studied in the presence of growth medium containing poultry feed waste (5%), K2HPO4 (0.3%), CaCl2 (0.03%) and MgSO4 (0.015%). Maximum protease production (264.25 ± 1.86 U/ml) was observed at initial pH 9 with 3% (v/v) of inoculum size after 48 h of incubation at 37 °C. The alkaline protease was stable over a broad range of temperature (30 to 60 °C) and pH (8 to 11). However, maximum activity (155.45 U/ml) was observed at temperature 50 °C and pH 10.Keywords: